2021
DOI: 10.1111/jan.14720
|View full text |Cite
|
Sign up to set email alerts
|

A systematic meta‐thematic synthesis to examine the views and experiences of women following water immersion during labour and waterbirth

Abstract: Aims:To gather, quality assess, synthesize and interpret the views, feeling, and experiences of women who used water immersion during labour and/or birth.Design: A systematic meta-thematic synthesis and GRADE-CERQual.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…The women in this research found that using water immersion in labour and for birth had a positive impact on their experience of birth. The findings of this research align with the existing literature regarding the effectiveness of water as a strategy for pain relief in labour (Carlsson & Ulfsdottir, 2020;Clews et al, 2019;Fair et al, 2020;Feeley et al, 2021;Gayiti et al, 2015;Maude & Foureur, 2007;Richmond, 2003;Ulfsdottir et al 2018). This research also supports the findings within the existing literature regarding the sanctuary and privacy which water immersion can provide for women during labour and birth (Clews et al, 2020;Fair et al, 2020;Maude & Foureur, 2007, Richmond, 2003Ulfsdottir et al, 2018, Ulfsdottir et al, 2019.…”
Section: Revision Of Research Aim and Findingssupporting
confidence: 86%
See 3 more Smart Citations
“…The women in this research found that using water immersion in labour and for birth had a positive impact on their experience of birth. The findings of this research align with the existing literature regarding the effectiveness of water as a strategy for pain relief in labour (Carlsson & Ulfsdottir, 2020;Clews et al, 2019;Fair et al, 2020;Feeley et al, 2021;Gayiti et al, 2015;Maude & Foureur, 2007;Richmond, 2003;Ulfsdottir et al 2018). This research also supports the findings within the existing literature regarding the sanctuary and privacy which water immersion can provide for women during labour and birth (Clews et al, 2020;Fair et al, 2020;Maude & Foureur, 2007, Richmond, 2003Ulfsdottir et al, 2018, Ulfsdottir et al, 2019.…”
Section: Revision Of Research Aim and Findingssupporting
confidence: 86%
“…Women with low-risk pregnancies using water immersion in labour have reported that it provides significant pain relief both during and between contractions and supports feelings of relaxation and ease during labour and birth (Carlsson & Ulfsdottir, 2020;Fair et al, 2020;Feeley et al, 2021;Liu et al, 2014;Maude & Foureur, 2007;Richmond, 2003;Ulfsdottir et al, 2018). Further, water immersion in labour provides support and buoyancy which supports movement in labour (Fair et al, 2020;Feeley et al, 2021;Maude & Foureur, 2007, Richmond, 2003Ulfsdottir et al, 2018). In addition, the sense of privacy and protection provided by water immersion supported the women in feeling like they were not handing themselves over to the process of birth but rather remaining in a position to work with, control and manage their labour in the way they required (Clews et al, 2020;Fair et al, 2020;Feeley et al, 2021;Maude & Foureur, 2007, Richmond, 2003Ulfsdottir et al, 2018, Ulfsdottir et al, 2019.…”
Section: Experience Of Water Immersion For Women With a Low-risk Preg...mentioning
confidence: 97%
See 2 more Smart Citations
“…The use of water immersion during labor and birth has been widely purported to support physiologic birth 6–11 . Laboring in water has been shown to provide a woman‐centered, low‐tech experience, 7–12 optimize physiology and relaxation, reduce pain, and increase maternal satisfaction with the birth experience 6,12–15 . Furthermore, studies demonstrate high levels of spontaneous vaginal birth, 10,12 and physiologic birth, 6,12 for healthy pregnant women, particularly in midwifery‐led settings.…”
Section: Introductionmentioning
confidence: 99%